Hematopoietic stem cell transplantation as rescue therapy for refractory autoimmune retinopathy: a case report - Wong, Wendy Meihua; Loh, Yvonne; Chan, Hwei Wuen; Fong, Warren; Chee, Soon-Phaik; Koh, Adrian; Holder, Graham E. (Frontiers in Immunology, 2025)
Autoimmune retinopathy (AIR) is a rare, potentially blinding retinal disease that remains a challenging condition to manage when resistant to conventional immune-modulatory approaches. We report clinical and electrophysiological improvement in a 49-year-old patient who underwent an autologous hematopoietic stem cell transplant (aHSCT) for thymoma-associated AIR after experiencing progressive disease despite receiving periocular and systemic steroids, mycophenolate mofetil, baricitinib, tacrolimus, bortezomib, rituximab, plasmapheresis, and intravenous immunoglobulin. The aHSCT had two stages: (i) peripheral blood stem cell harvest following mobilization with cyclophosphamide and granulocyte colony-stimulating factor, and (ii) conditioning regimen with plasmapheresis, rituximab, cyclophosphamide, and anti-thymocyte globulin high-dose therapy, followed by autologous hematopoietic cell infusion of 5.74 million cells. Symptoms of photopsia rapidly abated after undergoing aHSCT, and objective investigations of structure and function similarly demonstrated improvement. At 22 months’ follow-up, she continued to demonstrate the durability of the clinical response. The present report suggests that in judiciously selected patients, HSCT may provide a rescue option for refractory AIR. Further cases are needed to confirm these results.